2003
DOI: 10.1074/jbc.m307149200
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatase MKP1 Is a Transcriptional Target of p53 Involved in Cell Cycle Regulation

Abstract: The tumor suppressor p53 protein suppresses cell growth by inducing cell cycle arrest or apoptosis. Despite the fact that p53-dependent p21-mediated G 1 arrest induced by DNA damage is well defined, the role of p53 in the cell cycle in response to the MAKP signaling remains to be determined. Here we show that MKP1, a member of the dual specificity protein phosphatase family capable of inactivating MAPKs, is a transcriptional target of p53. MKP1 mRNA and protein levels were increased upon p53 activation in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 69 publications
(73 reference statements)
5
110
0
Order By: Relevance
“…This is suggested by the rapid decrease in the extent of phosphorylation of Ser 64 in vivo (Figure 1b) at a time when there is only a modest inhibition of protein kinase activity directed towards this site in in vitro assays (Figure 7b). Recently, several reports have shown that p53 is able to induce or activate novel protein phosphatases (Li et al, 2003;Ueda et al, 2003;Yin et al, 2003) but whether any of these act on 4E-BP1 remains to be established. It may be significant that the greatest p53-induced loss of phosphate from 4E-BP1 in vivo appears to involve Ser 64 , since this site can have a large influence on the binding of the protein to eIF4E (Mothe-Satney et al, 2000b;Karim et al, 2001) (although this conclusion has been challenged; Ferguson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested by the rapid decrease in the extent of phosphorylation of Ser 64 in vivo (Figure 1b) at a time when there is only a modest inhibition of protein kinase activity directed towards this site in in vitro assays (Figure 7b). Recently, several reports have shown that p53 is able to induce or activate novel protein phosphatases (Li et al, 2003;Ueda et al, 2003;Yin et al, 2003) but whether any of these act on 4E-BP1 remains to be established. It may be significant that the greatest p53-induced loss of phosphate from 4E-BP1 in vivo appears to involve Ser 64 , since this site can have a large influence on the binding of the protein to eIF4E (Mothe-Satney et al, 2000b;Karim et al, 2001) (although this conclusion has been challenged; Ferguson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of at least nine p53 target genes involved in cell-cycle regulation and/or apoptosis were also significantly altered by PBK knockdown. Among these were p21 (Bunz et al, 1998;Wendt et al, 2006), DUSP1 (Li et al, 2003) PBK/TOPK and p53 functional interactions F Hu et al (Pohl et al, 1999), FAS (Mu¨ller et al, 1998;Pohl et al, 1999), CASP10 (Rikhof et al, 2003) (all upregulated), and Bcl-xL (Bartke et al, 2001), which was downregulated. G2E3 (Brooks et al, 2007(Brooks et al, , 2008, a newly characterized gene involved in G 2 /M cell-cycle progression, was found to be suppressed by PBK knockdown, but its association to p53 is unknown.…”
Section: Gene Microarray Studiesmentioning
confidence: 99%
“…Also MKP1, the founding member of the dual-specificity protein phosphatase family, was found to be a direct transcriptional target of p53. 46 Functional studies revealed a marked influence of this phosphatase on p53-mediated cell cycle arrest. Whereas inhibition of its phosphatase activity by vanadate impaired p53-mediated G1-arrest in human glioblastoma cells in response to growth factor stimuli, conditional expression of MKP1 prevented arrested human lung cancer cells from entering into the cell cycle.…”
Section: P53 and Mitogen-activated Protein Kinasesmentioning
confidence: 99%